Prognostic value of a left atrioventricular coupling index in pre- and post-menopausal women from the Multi-Ethnic Study of Atherosclerosis - Pezel, Théo; Michos, Erin D.; Varadarajan, Vinithra; Shabani, Mahsima; Venkatesh, Bharath Ambale; Vaidya, Dhananjay; Kato, Yoko; De Vasconcellos, Henrique Doria; Heckbert, Susan R.; Wu, Colin O.; Post, Wendy S.; Bluemke, David A.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Sex hormones associated with both the left atrial (LA) and left ventricular (LV) structures in women, but the association of menopause status with left atrioventricular coupling is not established. Aim To assess the prognostic value of a left atrioventricular coupling index (LACI) in peri-menopausal women without a history of cardiovascular disease (CVD). Materials and methods In all women participating in MESA study with baseline cardiovascular MRI, the LACI was measured as the ratio of the LA end-diastolic volume to the LV end-diastolic volume. Cox models were used to assess the association between the LACI and the outcomes of atrial fibrillation (AF), heart failure (HF), coronary heart disease (CHD) death, and hard CVD. Results Among the 2,087 women participants (61 ± 10 years), 485 cardiovascular events occurred (mean follow-up: 13.2 ± 3.3 years). A higher LACI was independently associated with AF (HR 1.70; 95%CI [1.51–1.90]), HF (HR 1.62; [1.33–1.97]), CHD death (HR 1.36; [1.10–1.68]), and hard CVD (HR 1.30; [1.13–1.51], all p < 0.001). Adjusted models with the LACI showed significant improvement in model discrimination and reclassification when compared to traditional models to predict: incident AF (C-statistic: 0.82 vs. 0.79; NRI = 0.325; IDI = 0.036), HF (C-statistic: 0.84 vs. 0.81; NRI = 0.571; IDI = 0.023), CHD death (C-statistic: 0.87 vs. 0.85; NRI = 0.506; IDI = 0.012), hard CVD (C-statistic: 0.78 vs. 0.76; NRI = 0.229; IDI = 0.012). The prognostic value of the LACI had a better discrimination and reclassification than individual LA or LV parameters. Conclusion In a multi-ethnic population of pre- and post-menopausal women, the LACI is an independent predictor of HF, AF, CHD death, and hard CVD. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT00005487].